The Effect of Auditor Experience, Client Business Understanding, and Auditor Professional Skepticism on Fraud Detection Ability - Komang Ayu Devi, Ni; Luh Sari Widhiyani, Ni (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study analyzes the influence of auditor experience, client business understanding, and auditor professional skepticism on fraud detection ability at Public Accounting Firms (KAP) in Bali. The theoretical frameworks applied include the Fraud Triangle Theory and Attribution Theory. The study involved 71 auditors selected through purposive sampling. Data was collected using direct distribution of questionnaires. Analysis utilized multiple linear regression with SPSS 26. Findings demonstrate that auditor experience, client business understanding, and auditor professional skepticism positively affect fraud detection ability.